Spectrophotometric Assay of Paracetamol in Pharmaceutical Preparations - Nabeel Sabeh Othman; Safaa Abdul Aleem Zakaria (College of Education for Pure Sciences, 2007)
ABSTRACT A spectrophotometric method for the assay of micro amounts of paracetamol has been developed. The method is based on the reaction of p-aminophenol which results from the acid hydrolysis of paracetamol, with nitrite ion to form the corresponding diazonium salt followed by coupling reaction in an alkaline medium with phloroacetophenone to form a stable and soluble orange azo dye. The intensity of absorbance for the resulting azo dye is measured at 472 nm and Beer's law is obeyed in the concentration range of 10-180 g of paracetamol in a final volume of 25 ml, with a molar absorptivity of 2.16104 l.mol-1.cm-1, a relative error of -0.64 to +1.64% and a relative standard deviation of 0.4 to 1.24 %, depending on the concentration level of paracetamol. The method has been successfully applied to the assay of paracetamol in various pharmaceutical preparations.